Effects of imagery training on Concentration and Performance of Karate Kata Athletes based on Gender Review - Fauzi Ibrahim; Yadi Sunaryadi; Sagitarius; Mulyana (Universitas Negeri Semarang, 2024)
Psychological factors are one of the factors that support athlete performance. Therefore, there is a need for psychological training to overcome various psychological problems, especially the concentration and performance of karate athletes. This study aims to examine the effect of imagery training on the concentration and performance of kata karate athletes based on gender. This research uses an experimental method with a post-test only design. The sample used in this research was 10 karate kata Gokasi athletes from Bandung City, consisting of 5 female and 5 male athletes aged 11-13 years. Intensive imagery training was given as a research treatment, where they would imagine detailed word movements with an exercise duration of 10-15 minutes per session, frequency 3-4 times a week for 4 weeks. Measurements were carried out in two aspects, namely concentration using the Concentration Grid Test (CGT) and performance using the jury’s assessment through mini-events. Data analysis was carried out using the SPSS Version 27 statistical test. The results of the study showed that the impact of visualization training on the focus and performance of karate kata athletes, both male and female, varied greatly. Male athletes outperformed female athletes in the concentration variable, while female athletes outperformed male athletes in the performance variable. Thus, it can be said that imagination training is one of the exercises that can be used to help karate kata athletes, both male and female, to be more focused and perform better.